Development of declarative and procedural knowledge test - Miščević-Kadijević Gordana (Psihologija, 2009)
Teacher training faculty, University of Belgrade, Serbia The paper presents the development of a knowledge test, designed for ten-year old pupils, that measures the attainment of declarative and procedural knowledge about human body acquired through a fourth-grade course on nature and society. The final version comprising sixteen tasks, had desired factor structure evidenced by the applied confirmatory factor analysis as well as appropriate metric characteristics of reliability, discriminativity and objectivity. Apart from the metric characteristics of the whole test and its two knowledge subtests as regards reliability, this paper also reports the discriminativity of particular tasks. The reported characteristics evidence that a solid instrument has been developed.